PERSEPSI MASYARAKAT TERHADAP KERUSAKAN TERUMBU KARANG DI TELUK AMBON DALAM - Eygner Gerald Talakua (Universitas Pattimura, 2020)
The coral reefs in Inner Ambon Bay are in the bad category or can even be said to be almost gone where the percentage of coral cover is very small. Efforts to deal with damage to coral reefs have been carried out through rehabilitation programs in Ambon Bay. One of the recommendations given through this program is the need for the participation of coastal communities near the coral transplantation site. It is expected that a good / positive community perception of the existence of coral reefs will encourage the community to participate in efforts to repair damaged coral reefs. For this reason, this research aims to assess public perceptions of damage to coral reefs in Inner Ambon Bay. The survey method was conducted on 318 samples of household heads for primary data collection using a Likert scale questionnaire. The data is analyzed qualitatively and quantitatively. The results showed that people's perception of coral reefs in Inner Ambon Bay was